Vitamin C in Stem Cell Biology: Impact on Extracellular Matrix Homeostasis and Epigenetics - Cristina D'Aniello; Federica Cermola; Eduardo Jorge Patriarca; Gabriella Minchiotti (Hindawi Limited, 2017)
Transcription factors and signaling molecules are well-known regulators of stem cell identity and behavior; however, increasing evidence indicates that environmental cues contribute to this complex network of stimuli, acting as crucial determinants of stem cell fate. L-Ascorbic acid (vitamin C (VitC)) has gained growing interest for its multiple functions and mechanisms of action, contributing to the homeostasis of normal tissues and organs as well as to tissue regeneration. Here, we review the main functions of VitC and its effects on stem cells, focusing on its activity as cofactor of Fe+2/αKG dioxygenases, which regulate the epigenetic signatures, the redox status, and the extracellular matrix (ECM) composition, depending on the enzymes' subcellular localization. Acting as cofactor of collagen prolyl hydroxylases in the endoplasmic reticulum, VitC regulates ECM/collagen homeostasis and plays a key role in the differentiation of mesenchymal stem cells towards osteoblasts, chondrocytes, and tendons. In the nucleus, VitC enhances the activity of DNA and histone demethylases, improving somatic cell reprogramming and pushing embryonic stem cell towards the naive pluripotent state. The broad spectrum of actions of VitC highlights its relevance for stem cell biology in both physiology and disease.